(untitled) (Scientia Agropecuaria, 2013)
The objective of this study was to determine the stability of commercial and experimental maize hybrids in the Central Ecuadorian Coastal Region. During a period from december 2010 to april 2011 uniform trials of yield in four locations with contrasting environments were evaluated. The genetic material was constituted by five experimental hybrids and three commercial. The experimental design used was completely randomized blocks design with four replications; the experimental plots were two rows with a length of 5.0 m separated to 0.90 meters. The combined analysis of variance proposed by Eberhart and Russel was statistical significance as well as for genotype and for interaction. The average yield showed that between experimental hybrids two, (SM45 x SSD08)SV39 and (SM45 x SV15)SV39, were highlighted with averages higher than 7.0 t ha-1 whilst AG-003 was the highlighted commercial hybrid with a yield of 7.48 t ha-1. The best yields and environmental indexes were registered in the locations of Quevedo and Vinces, the lowest environmental indexes were for Balzar and Ventanas. In relation to the tendency of response of the outstanding genotypes in the four evaluation environments, it was particularly observed that genotypes are desirable by virtue of the outstanding results in both favorable and unfavorable environments.